2009
DOI: 10.1021/bm9006979
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silver Nanoparticles Templated by TEMPO-Mediated Oxidized Bacterial Cellulose Nanofibers

Abstract: We have prepared silver nanoparticles on the surface of bacterial cellulose (BC) nanofibers. The synthesis of silver nanoparticles incorporates 2,2,6,6-tetramethylpiperidine-1-oxyradical (TEMPO)-mediated oxidation to introduce carboxylate groups on the surface of BC nanofibers. An ion exchange of the sodium to the silver salt was performed in AgNO(3) solution, followed by thermal reduction. By using oxidized BC nanofibers as a reaction template, we have prepared stable silver nanoparticles with a narrow size d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
170
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(173 citation statements)
references
References 26 publications
2
170
0
1
Order By: Relevance
“…It indicated that TEMPO was not as effective as APS on cellulose oxidation. Moreover, CNCs from TEMPO oxidation are highly carboxylated [114,115], which provides the opportunity for functionalization [116,117].…”
Section: Oxidation Degradationmentioning
confidence: 99%
“…It indicated that TEMPO was not as effective as APS on cellulose oxidation. Moreover, CNCs from TEMPO oxidation are highly carboxylated [114,115], which provides the opportunity for functionalization [116,117].…”
Section: Oxidation Degradationmentioning
confidence: 99%
“…Few solutions were proposed for that phenomenon, which are controlled deposition of metal particles through hybridization using nanoporous materials serving as templates, which preserve the well-defined spatial distribution [87]. The shape of bacterial cellulose may ease the incorporation of nanoparticles of metals [88]. Few studies were done to determine such possibility like impregnation the bacterial cellulose with silver nanoparticles by triethanolamine (TEA) [89]; NaBH4 and UV radiation [64]; moreover by application of hydrazine, hydroxyl amine or ascorbic acid [90] as well as by self-polymerized polydopamine [91] and TEMPO-mediated oxidized BC followed by thermal reduction [88].…”
Section: Chemical Elements As a Solution For Poor Bc Antimicrobial Acmentioning
confidence: 99%
“…Additionally it is well known that silver is strongly attracted by cellulose and this has been widely used to synthesize large and plasmonic silver nanoparticles. [50,[58][59][60] In this regard, the formation of the composite NFC/AgNC could hypothetically be due to a transfer of AgNC from PMAA chains to cellulose nanofibers. However, this hypothesis is unlikely because the transfer of AgNC reported in literature is typically accompanied with a large shift in the optical bands, whereas in the present case, the shift observed in the emission peak of AgNC when mixed with NFC dispersions is small (not shown).…”
Section: Mechanism Of Composite Formation Between Native Cellulose Namentioning
confidence: 99%